2014
DOI: 10.1016/j.taap.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Differential metabolism of 4-hydroxynonenal in liver, lung and brain of mice and rats

Abstract: The lipid peroxidation end-product 4-hydroxynonenal (4-HNE) is generated in tissues during oxidative stress. As a reactive aldehyde, it forms Michael adducts with nucleophiles, a process that disrupts cellular functioning. Liver, lung and brain are highly sensitive to xenobiotic-induced oxidative stress and readily generate 4-HNE. In the present studies, we compared 4-HNE metabolism in these tissues, a process that protects against tissue injury. 4-HNE was degraded slowly in total homogenates and S9 fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…Li et al (2011a) observed in mouse pulmonary cytosol GST activity toward ethylene oxide as substrate. Zheng et al (2014) observed that GST specific activity toward the prototypic substrate 4-hydroxynonenal was very high in mouse lung 9000 g supernatant, almost as high as in the liver.…”
Section: Enzymatic Activitymentioning
confidence: 95%
“…Li et al (2011a) observed in mouse pulmonary cytosol GST activity toward ethylene oxide as substrate. Zheng et al (2014) observed that GST specific activity toward the prototypic substrate 4-hydroxynonenal was very high in mouse lung 9000 g supernatant, almost as high as in the liver.…”
Section: Enzymatic Activitymentioning
confidence: 95%
“…Consistently Zheng et al also found that lung and brain in rat and mouse showed limited activity of HNE degradation by alcohol/aldehyde dehydrogenase compared to liver [28]. In addition, GST expression level and activity also vary with tissues [28]. Such variation in HNE metabolizing activity in different tissues means that HNE concentration may vary from tissue to tissue in vivo.…”
Section: Tissue Concentration Of Hnementioning
confidence: 78%
“…The last had less than 3% of the HNE metabolizing activity of liver, largely due to the lack of alcohol/aldehyde dehydrogenase activity in these tissues [25]. Consistently Zheng et al also found that lung and brain in rat and mouse showed limited activity of HNE degradation by alcohol/aldehyde dehydrogenase compared to liver [28]. In addition, GST expression level and activity also vary with tissues [28].…”
Section: Tissue Concentration Of Hnementioning
confidence: 98%
See 1 more Smart Citation
“…Medicinal plants and bioactive compounds are found to enhance metabolism, detoxification or clearance of 4-HNE by regulating activities of endogenous enzymes (such as AR, GST, and AKRs), which may provide the effective strategies for combating 4-HNE-driven deleterious effects. Because of differential metabolisms of 4-HNE observed in liver, lung, and brain of rodents [130], further study is warranted to determine whether these medicinal plants and bioactive compounds have the capacity to mediate oxidative, reductive, and conjugative pathways to metabolize 4-HNE and 4-HNE adducts in oxidative stress-triggered injury of these tissues.…”
Section: The Strategy For Developing Potential Therapymentioning
confidence: 99%